THE ROLE OF THE TEACHER IN DEVELOPING SKILLS LITERACY READING AND WRITING CLASS IV STUDENTS STATE 23 PRIMARY SCHOOL BANDA ACEH - Gaja, Dama Darni; Israwati, Israwati; Hasniyati, Hasniyati (Elementary Education Research, 2024)
The problem in this research is "What is the Role of Teachers in Developing the Reading and Writing Literacy Skills of Class IV Students at SD Negeri 23 Banda Aceh". This research aims to describe the role of teachers in developing the reading and writing literacy skills of class IV students at SD Negeri 23 Banda Aceh. The approach used in this research is a qualitative approach with descriptive research type. This research was conducted at SD Negeri 23 Banda Aceh with 35 students as subjects, there were 25 students in the good category, 6 students in the fair category, 4 students in the failed category, and no students in the failed category.